2019
DOI: 10.1186/s12936-019-2778-y
|View full text |Cite
|
Sign up to set email alerts
|

Does anthropometric status at 6 months predict the over-dispersion of malaria infections in children aged 6–18 months? A prospective cohort study

Abstract: Background In malaria-endemic settings, a small proportion of children suffer repeated malaria infections, contributing to most of the malaria cases, yet underlying factors are not fully understood. This study was aimed to determine whether undernutrition predicts this over-dispersion of malaria infections in children aged 6–18 months in settings of high malaria and undernutrition prevalence. Methods Prospective cohort study, conducted in Mangochi, Malawi. Six-months-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Likewise, food insecurity had mixed associations with general infant health status in two studies conducted within a high‐income country (Hernandez & Jacknowitz, 2009 ; Neault et al, 2007 ). Single studies in low‐ and lower‐middle‐income countries, however, consistently found that food insecurity was associated with a greater risk of illness, including positive associations with infant mortality (Campbell et al, 2009 ), cough (Ohemeng et al, 2015 ), malaria infection (Bendabenda et al, 2019 ) and nasal discharge (Ohemeng et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, food insecurity had mixed associations with general infant health status in two studies conducted within a high‐income country (Hernandez & Jacknowitz, 2009 ; Neault et al, 2007 ). Single studies in low‐ and lower‐middle‐income countries, however, consistently found that food insecurity was associated with a greater risk of illness, including positive associations with infant mortality (Campbell et al, 2009 ), cough (Ohemeng et al, 2015 ), malaria infection (Bendabenda et al, 2019 ) and nasal discharge (Ohemeng et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%